2019
DOI: 10.1088/1757-899x/518/3/032018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of velocity distribution utilizing the helically coiled tape in a conical diffuser

Abstract: Numerical analyses study is reported on the flow characteristics in a conical diffuser with a helical tape insert. In this study, a rectangular tape of 5 mm width and 2 mm thickness is used inside the inner wall of the diffuser to induce additional recirculation. The numerical results are achieved for different Reynolds numbers (58035, 116072, 174108 and 232144) based on the inlet hydraulic diameter. The simulations are carried out with constant inlet condition considering the flow turbulent and incompressible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The use of this method made it possible to suppress massive flow separation in the diffuser's expansion section and in the downstream area, as well as to increase the efficiency of pressure recovery in a CD. There are also studies on the development of various structural elements in a diffuser to ensure a more uniform flow along the entire length of the CD [24,25]. For example, E. S. Shukri installed a screw tape or spiral-screw insert on the inner surface of the conical diffuser to level the velocity field [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this method made it possible to suppress massive flow separation in the diffuser's expansion section and in the downstream area, as well as to increase the efficiency of pressure recovery in a CD. There are also studies on the development of various structural elements in a diffuser to ensure a more uniform flow along the entire length of the CD [24,25]. For example, E. S. Shukri installed a screw tape or spiral-screw insert on the inner surface of the conical diffuser to level the velocity field [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies on the development of various structural elements in a diffuser to ensure a more uniform flow along the entire length of the CD [24,25]. For example, E. S. Shukri installed a screw tape or spiral-screw insert on the inner surface of the conical diffuser to level the velocity field [24,25]. A numerical study showed a significant effect in improving the uniformity of velocity distribution throughout the entire volume of the diffuser compared to CDs without such inserts.…”
Section: Introductionmentioning
confidence: 99%